CYBER SECURITY AND ECONOMIC SECURITY: RELATIONSHIPS AND CHALLENGES - Abdumannab, Yusufjonov Temurbek; Rustambek, Rustambekova Feruza (Journal of Innovation in Education and Social Research, 2024)
The modern world has witnessed a significant increase in the number of cyber threats that can affect the economic security of the state. Cybersecurity and economic security are closely related, and the interaction between them plays an important role in ensuring the stability of the economy. This article examines the relationship between cyber security and economic security and the challenges they face.